Analysis of the Role of Social Services in Handling Homeless Beggars (GEPENG) in Medan City (Case Study of Medan City Social Service) - Sudiarti, Sri; Nasution , Eldzan Izzahara (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Poverty is generally caused by the powerlessness of a person at working age, as well as the difficulty of getting a job or termination of employment due to the economic crisis that results in unemployment. Positive and negative impacts seem to be increasingly difficult to avoid in development, so efforts are needed to further develop the positive impacts of development and reduce and anticipate the negative impacts. Homeless beggars are one of the negative impacts of development, especially urban development. Homeless urban beggars are a phenomenon that is starting to be seen as a serious problem, especially with the increasing number of social problems. The problem of homeless beggars is a social phenomenon that cannot be avoided, especially in the city of Medan. The social service is an element of government implementation that is authorized in activities in the social sector. The Social Service carries out the functions of administering government affairs and public services in the fields of social rehabilitation and social protection guarantees, social empowerment and handling the poor. With so many homeless and beggars circulating in the city of Medan, the role of the Social Service is very much needed in overcoming this problem. This study aims to find out how the role of social services in handling homeless and beggars (sprawl) in Medan City. This study uses a qualitative-descriptive method to describe and explain the role of the Social Service in handling homeless people and beggars in the city of Medan.